The kicking performance by different boots material - Ahmad, Z.; Pi Remli, M. A.; Nordin, M. H.; Johari, N. H. (Journal of Human Sport & Exercise, 2015)
The purpose of this study was to investigate the kinematics of kicking by experimental and simulation techniques analysis. The differences of material stiffness will affected to the ball velocities. Experimental setup by high speed video camera with 250 frames per second was performed in order to obtain the foot and ball velocities during the kicking process. There are 10 male football players from Majlis Sukan Negeri Terengganu (MSNT) were selected as subjects. Instep kicking with right foot was choosing due to the highest ball velocities can be produced by this technique. Simulation analysis by finite element analysis (FEA) then used to validate the results from experimental work done. Polyethylene material and 2.0mm thickness from boot C was considered as the best boot design compared to the others. It gives the highest maximum stress and the highest force to produce the highest ball velocity. The other variables related to the ball velocity such as coefficient of restitution (COR) and contact time. This study is useful to design the suitable material for each region of boots. It also can help the athletes to identify the characteristics of boot selection for different position on the field.